MANAJEMEN KOMUNIKASI ANTARA GURU DAN ORANG TUA DALAM MENINGKATKAN PROSES PEMBELAJARANDI MI TAHFIDZ ANWARUL HASANIYYAH - Atila Nurkhatiqah; Dhiya Rahmatina, Istiqamah, Syahrani (CV. ADIBA AISHA AMIRA, 2023)
Improving the learning process at MI Tahfidz Anwarul Hasaniyyah is influenced by many factors, one of which is the communication management process between teachers and parents. Good communication between teachers and parents is very influential on the smoothness of learning. In this communication, social media such as WhatsApp is needed as a communication tool. This research uses a quantitative approach in the form of frequency distribution.